2012
DOI: 10.1186/1556-276x-7-590
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of nitrogen/sulfur co-doped TiO2 nanocrystals with a high specific surface area and a high percentage of {001} facets and their enhanced visible-light photocatalytic performance

Abstract: Nitrogen/sulfur co-doped anatase TiO2 nanocrystals with a high specific surface area and a high percentage of {001} facets were synthesized by a solvent-thermal process followed by the calcination with thiourea at an optimum heat treatment temperature. Under current experimental conditions, the optimum heat treatment temperature was found at 300°C, which successfully introduced nitrogen and sulfur dopants into the anatase lattice to replace a small portion of oxygen atoms while preserving the geometry of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Advanced oxidation processes (AOPs) are promising and environmentally friendly wastewater treatment technologies capable of mineralizing deleterious substances in wastewater systems [4,[8][9][10]. Among all, photocatalysis, especially with titanium dioxide (TiO 2 ), is commonly studied owing to its high chemical stability, promising efficiency, low cost, and non-toxicity [10][11][12]. The study conducted by Sang et al showed promising efficiency of TiO 2 in degrading the artificial sweeteners found in confectionery wastewater and in mineralizing the intermediate products generated during the degradation process [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced oxidation processes (AOPs) are promising and environmentally friendly wastewater treatment technologies capable of mineralizing deleterious substances in wastewater systems [4,[8][9][10]. Among all, photocatalysis, especially with titanium dioxide (TiO 2 ), is commonly studied owing to its high chemical stability, promising efficiency, low cost, and non-toxicity [10][11][12]. The study conducted by Sang et al showed promising efficiency of TiO 2 in degrading the artificial sweeteners found in confectionery wastewater and in mineralizing the intermediate products generated during the degradation process [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of TiO 2 is limited by the ultraviolet (UV) activation and the fast recombination rate of the generated electron-hole pairs [10,12,14]. Hence, modifications of TiO 2 photocatalysts through metal doping, non-metal doping, and its combination with another semiconductor photocatalyst are common methods to extend the absorption wavelength of TiO 2 towards visible light spectrum, to restrict the recombination of electron-hole pairs, and to increase the specific surface area of the photocatalyst [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, anatase TiO 2 nanocrystals with exposed facets were developed, which demonstrated enhanced photocatalytic performance than their counterparts in the micrometer size range due to their largely increased surface areas [14][15][16][17][18]. It was found that the photocatalytic activity of anatase TiO 2 could be further modulated by incorporating different exposed crystal facets [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the partial overlapping of S 2 p 3/2 and S 2 p 1/2 , XPS signals associated with the substituted sulfur ( S sub ) should be found in the 159.8 eV–165.4 eV range (peak I) . The peak around 169 eV (peak II) corresponds to the S species adsorbed on the N/S‐TiO 2 ,…”
Section: Resultsmentioning
confidence: 99%